Essential Oils: A Natural Therapy for the Treatment of Cancer - Rohilla, Sulekha; Singh, Seemu; Hazra, Abhijit (Pharmacognosy Reviews)
Nature has always played a significant role in the treatment of various diseases including cancer, one of the most significant health challenges in the world nowadays. Among the available natural products used in therapy natural essential oil constituents play a key role in the prevention and treatment of cancer. Natural essence in the form of essential oil has been explored comprehensively by various groups of researchers in the field of cancer treatment. It works via several mechanisms such as antioxidant, anti-mutagenic, anti-proliferative, etc. for their chemo preventive action. Even aromatherapy with the use of essential oils has been widely employed to reduce the complications occurring during cancer/chemotherapy treatment like nausea, vomiting, etc. This review focuses on the various constituents of essential oils with their potential therapeutic efficacy against cancer along with their potent mechanism of action.
Keywords: Cancer; Essential oil; Anti-proliferative; Aromatherapy